The erythrocyte sedimentation rate (ESR) in canine inflammation. (April 2023) - Gori, E.; Pierini, A.; Pasquini, A.; Diamanti, D.; Carletti, C.; Lubas, G.; Marchetti, V.
Abstract: The clinical application of the erythrocyte sedimentation rate (ESR) assay is challenging due to its long processing time. However, in 2020 a new automated instrument for veterinary ESR was released and validated. This study sought: (1) to refine the proposed reference range (reference interval, RI) for canine ESR; (2) to compare the ESR values of healthy and sick dogs; and (3) to correlate ESR with other inflammatory markers such as C-reactive protein (CRP), fibrinogen, albumin:globulin ratio (A/G), and neutrophil-to-lymphocyte ratio (NLR); and also (4) to study ESR behavior across illnesses of varying durations. A prospective cohort study of 396 client-owned dogs ( n  = 120 healthy and n  = 276 sick dogs) was conducted. Animals with a full clinical evaluation, complete hematobiochemical profile and a final diagnosis were included. ESR was performed according to manufacturer's instructions using the same 1 mL K3-EDTA tube used for the complete blood count. The RI was established at 1–8 mm/h in 14 min. Sick dogs had a significantly faster ESR (median 10 mm/h) than healthy dogs (median 1 mm/h; P  < 0.0001). ESR was positively correlated with NLR ( r  = 0.36), CRP ( r  = 0.18) and fibrinogen ( r  = 0.56) and negatively correlated with A/G ( r  = −0.37). Dogs with an acute-on-chronic disease had the highest ESR values (median 17 mm/h) compared with either acute (median 11 mm/h; P < 0.001) or chronic diseases (median 7 mm/h; P  = 0.001). ESR was confirmed as a reliable canine inflammatory marker, positively correlating with the main inflammatory markers in dogs and significantly different between sick and healthy dogs. The ESR assay appears useful especially in dogs with an acute clinical presentation, with or without an underlying chronic condition. Highlights: Inflammatory marker testing is valuable in canine clinical pathology. A novel automated erythrocyte sedimentation rate (ESR) assay has been validated. For healthy dogs, the ESR reference interval was determined as 1–8 mm/h. Sick dogs had faster ESR (median 10 mm/h) than healthy dogs (median 1 mm/h). ESR was correlated with other inflammatory markers, especially fibrinogen.